Correlation between Blood Pressure and Obesity Parameter against Cystatin-C and Adiponectin Levels in Serum of Obese Adolescent - Ridwan Ridwan; Ami Febriza; Elmiana Bongga Linggi; Rosdiana Natzir; Nurpudji Astuti Tazlim (Molecular and Cellular Biomedical Sciences, 2020)
Background: Obesity contributes to the increased risk of chronic kidney and systemic inflammation. This condition can occur in obese adolescents. Most researches of cystatin-C (cys-C) and adiponectin have been carried out in adult and children subjects. The purpose of this research is to determine differences in serum cys-C and adiponectin levels between obese and normoweight adolescents and their correlation with blood pressure and obesity parameters.Materials and Methods: Twenty-eight obese adolescents and 22 normoweight adolescents aged 15-18 years old participated in this research. After the measurement of blood pressure and obesity parameters, we examined serum cys-C levels as a biomarker for decreased early stage renal function and adiponectin, an antiinflammatory adipokine. Estimated glomerular filtration rate (eGFR) based on serum cys-C is calculated using the eGFR-Chronic Kidney Disease Epidemiology Collaboration (eGFR-CKD EPI cys-C equation formula). Results: Cys-C levels in obese adolescents were higher than normoweight adolescents. In contrast, serum adiponectin levels in obese adolescents were lower than for normoweight adolescents. Interestingly, eGFR based on serum cys-C showed no difference, although eGFR in obese adolescents was lower than normoweight adolescent. Serum cys-C was positively correlated with systolic blood pressure (SBP), diastolic blood pressure (DBP), body mass index (BMI) and waist circumference (WC). Serum adiponectin was negatively correlated with SBP, DBP, BMI and WC. SBP is a predictor factor for the increase in serum cys-C and BMI is a predictor factor in the decrease in serum adiponectin levels. Conclusion: There is a decline in early stage kidney function and inflammation in obese adolescents as evidenced by increased serum cyst-C levels and decreased serum adiponectin levels. These two biomarkers correlate with blood pressure, BMI and WC and play a role in the pathomechanism of early stage impairment of kidney function and inflammation in obese adolescents.Keywords: adiponectin, body mass index, cystatin-C, early stage renal diseases, inflammation, systolic blood pressure